RANCANG BANGUN SISTEM INFORMASI PERAWATAN MESIN PRODUKSI KERAMIK DAN GRANIT PADA PT.JUISHIN INDONESIA - ADNAN Buyung Nasution (Jurnal Informatika Kaputama (JIK), 2019)
Care information system is the application of technology that many do at this time is none other eraglobalisasi to help care reporting system administration in a structured and automatic machines, as well as in this study conducted implementation of information systems production machinery maintenance ceramic and granite machines at PT. Juishin Indonesia where to do the implementation of information systems to minimize the problems that are often experienced in doing the preparation of the administration of production machinery maintenance including difficulty in entering the data with terestruktur due in data storage does not use the database system so that it will menylitkan in preparing the report well, but it also difficulty in searching the data based on specific production engine damage. By doing so, the goal of this research is done to facilitate the administration to perform data entry and also facilitate the search for the required data as information that affect the decision atasan.dan keputusa a conclusion in this research that the information system of ceramic production machinery maintenance and granite effective in its application.